Rhythm in the speech of a person with right hemisphere damage: Applying the pairwise variability index - Knight, R.; Cocks, Naomi (Taylor and Francis, 2007)
Although several aspects of prosody have been studied in speakers with right hemisphere damage (RHD), rhythm remains largely uninvestigated. This study compares the rhythm of an Australian English speaker with right hemisphere damage (due to a stroke, but with no concomitant dysarthria) to that of a neurologically unimpaired individual. The speakers' rhythm is compared using the pairwise variability index (PVI) which allows for an acoustic characterization of rhythm by comparing the duration of successive vocalic and intervocalic intervals. A sample of speech from a structured interview between a speech and language therapist and each participant was analysed. Previous research has shown that speakers with RHD may have difficulties with intonation production, and therefore it was hypothesized that there may also be rhythmic disturbance. Results show that the neurologically normal control uses a similar rhythm to that reported for British English (there are no previous studies available for Australian English), whilst the speaker with RHD produces speech with a less strongly stress-timed rhythm. This finding was statistically significant for the intervocalic intervals measured (t(8) = 4.7, p < .01), and suggests that some aspects of prosody may be right lateralized for this speaker. The findings are discussed in relation to previous findings of dysprosody in RHD populations, and in relation to syllable-timed speech of people with other neurological conditions.